0471 The Effect of Meal Timing on Sleep Parameters and Apnea Severity in Sleep Apnea Patients. (27th April 2018) - Lopes, Td; Borba, Md; Lopes, Rd; Paim, S L; Teodoro, V V; Fisberg, R; Zimberg, I Z; Crispim, C
Abstract: Introduction: Studies have demonstrated an association between meal timing and sleep duration; however, few studies have evaluated the effect of meal timing on sleep architecture and apnea severity in Obstructive Sleep Apnea (OSA) individuals. Therefore, the objective of this study was to evaluate the association of meal timing and sleep parameters and apnea severity in OSAS patients. Methods: A total of 296 OSAS patients were evaluated in a private clinic in a city of Minas Gerais State, Brazil. Meal timing were obtained in addition to a food frequency questionnaire (FFQ). Subjects were dichotomized in early and late eaters for breakfast, lunch and dinner using the median values of these meals in the population as the cut-off point. All the patients were interviewed before the overnight polysomnography examination. A generalized linear model (GLzMM), adjusted for confounders, was used in order to determine the effect of meal timing on sleep architecture and apnea severity Results: Breakfast timing was associated with Waking After Sleep Onset (WASO) (B= 3.567, CI= 1.243–5.892, p=0.003), stage N1 (B=0.130, CI= 0.060–0.199, p= 0.000) and REM sleep (B= -1.189, CI= -1.889 -0.490, p=0.001); lunch timing demonstrated association with latency (B= 0.293, CI= 0.124–0.463, p= 0.001) and stage N1 (B= 0.095, CI= 0.012–0.178, p=0.025); dinner timing showed association with latency (B= 0.130, CI= 0.019–0.241, p=0.022) and Apnea-Hypopnea Index (AHI) (B=1.284, CI= 0.102–2.466, p=0.033). Conclusion: In conclusion, meal timing had effects on sleep architecture as latency, WASO, stage N1, REM sleep, as well as on AHI. These data suggest that later eaters are more likely to present the worst sleep pattern and apnea severity. Support (If Any): Fundação de Amparo à Pesquisa de Minas Gerais (FAPEMIG) and CNPq.